Additive manufacture of anti-biofouling inserts for marine applications. Issue 2 (21st March 2016) - Leary, Martin; Piola, Richard; Shimeta, Jeff; Toppi, Steven; Mayson, Scott; McMillan, Matthew; Brandt, Milan
Abstract : Purpose: Biofouling of marine vessels results in significant operational costs, as well as the bio-security risk associated with the transport of marine pests. Biofouling is particularly rapid in sea-chest water intakes due to elevated temperatures and circulating flow. Inspection challenges are exacerbated, as sea chests are difficult to inspect and clean. This paper aims to present a method that utilises the flexibility and low-batch capabilities of additive manufacture to manufacture custom sea-chest inserts that eliminate circulating flow and increase the uniformity of shear stress distributions to enable more constant ablation of anti-biofouling coatings. Design/methodology/approach: An automated design procedure has been developed to optimise sea-chest insert geometry to achieve desirable flow characteristics, while eliminating the necessity for support material in FDM manufacture – thereby significantly reducing build cost and time. Findings: Numerical flow simulation confirms that the fluid-flow approximation is robust for optimising sea-chest insert geometry. Insert geometry can be manipulated to enable support-free additive manufacture; however, as the threshold angle for support-free manufacture increases, the set of feasible sea-chest aspect ratios decreases. Research limitations/implications: The surface of revolution that defines the optimal insert geometry may result in features that are not compatible with additive manufacture constraints. An alternate geometry is proposed that may be more useful in practice without compromising anti-biofouling properties. Practical implications: Marine sea-chest biofouling results in significant negative environmental and economic consequence. The method developed in this paper can reduce the negative impact of sea-chest biofouling. Social implications: Marine sea-chest biofouling results in significant resource consumption and emissions. The method developed in this paper can reduce the negative impact of sea-chest biofouling. Originality/value: The method presented in this paper provides an entirely original opportunity to utilise additive manufacture to mitigate the effects of marine biofouling.